Contribution of the Hague Principles on Choice of Law in International Commercial Contracts to the codification of party autonomy under OHADA Law. (2nd January 2019) - Monsenepwo, Justin
Abstract : The Organization for the Harmonization of Business Law in Africa (hereinafter referred to as OHADA) was created on 17 October 1993 to foster economic development in Africa by creating a uniform and secure legal framework for the conduct of business in Africa. In an effort to reform the law of contracts in its Member States, OHADA has prepared the Preliminary Draft of the Uniform Act on the Law of Obligations (hereinafter referred to as the Preliminary Draft). Several provisions of the Preliminary Draft set forth general principles concerning choice of law in international commercial contracts. Indeed, the Preliminary Draft encompasses innovative provisions on party autonomy in international contracts, such as the explicit recognition of the right of parties to choose the law applicable to their contracts and the inclusion of limited exceptions to party autonomy (overriding mandatory rules and public policy). Yet, it still needs to be improved in respect of various issues, including for instance the ability of parties to choose different laws to apply to distinct parts of their contract and the possibility for the parties to expressly include in their choice of law the private international law rules of the chosen law. This paper analyses the provisions of the Preliminary Draft in the light of the Hague Principles on Choice of Law in International Commercial Contracts (hereinafter referred to as the Hague Principles). More particularly, it explores how the Hague Principles can help refine the rules on party autonomy contained in the Preliminary Draft to enhance legal certainty and predictability in the OHADA region.